Electronic Tattoo with Transferable Printed Electrodes and Interconnects for Wireless Electrophysiology Monitoring. Issue 8 (21st January 2022) - Huttunen, Olli‐Heikki; Behfar, Mohammad H.; Hiitola‐Keinänen, Johanna; Hiltunen, Jussi
Abstract: The increasing need for wearable electrophysiological monitoring devices has motivated significant amount of research to develop electronic tattoos (e‐tattoo) enabling high comfortability and unobtrusive usage. Despite considerable advancements, challenges still remain that limit the device testing under clinical settings and consequently, the uptake to practical usage. A key challenge is the robust full signal pathway from the skin to the electronics device. Another factor limiting the concept testing with high number of test devices is the lack for scalable materials and processes comprising all manufacturing steps. The study presents a scalable manufacturing of self‐adhering tattoo electrodes and interconnects on transferable breathable polydimethylsiloxane (PDMS) substrate with the thickness of 30 µm. Transfer tattoo enables two‐sided signal pathway from the skin, in to the encapsulated conductor traces and provides exposed connection points to electronics. The e‐tattoos withstand repeated one thousand, 10% elongation cycles and the transfer substrate showed breathability comparable to commercial medical patches. The integration of flexible wireless ECG module with the skin‐mounted e‐tattoo is also demonstrated. The results enable the up‐scaled fabrication of robust e‐tattoos with integrated electronic modules that is prerequisite for the scientific studies relying on high number of test devices and industrial uptake of e‐tattoo concepts. Abstract : A transferable and self‐adhering electronic tattoo is developed for human electrophysiology monitoring. The tattoo consists of printed Ag interconnects and printed Ag/AgCl electrodes capsuled in a thinner than hair transfer substrate made of PDMS. The e‐tattoo is highly conformable and easy to mount on the skin. Integrated with stretchable module, the e‐tattoo shows excellent performance in ECG measurement.